Noise Level of Railroad Settlements JPL 05 Kaligawe Street, Semarang - Haryono Setiyo Huboyo; Nurandani Hardyanti; Fera Meilasari (Universitas Diponegoro, 2022)
Noise is unwanted sound at a particular time and is sourced from any source. Data from the Pusarpedal Laboratory and the Ministry of Environment and Forestry of the Republic of Indonesia show that railroad settlements' noise in Yogyakarta, Surabaya, Semarang, and Bandung is beyond quality standards. Tambakrejo Village, Gayamsari District, Semarang, one of the railroad settlements at JPL 05 Kaligawe Street, Semarang area, close to a railroad. This research aims to know the noise level of the settlements. The sampling of noise level is done for 24 hours by measuring the noise for each time interval, with a total of 16 measuring points for 4 areas with various distances, 2.5 m, 5 m, 10 m, and 15 m. The sampling result shows that the railroad settlements have a noise level rate of 91.8 dB at a distance of 2.5 m, 89.5 dB at 5 m, 85.2 dB at 10 m, and 81.5 dB at 15 m. According to NOISE REL regulation, the maximum noise level allowed is 85.57 dB during 421 minutes or 7.02-hour of exposure. This sampling result shows that the noise levels are beyond of quality standards of both NIOSH REL and PermenLH No. 48/1996.